L’autonomie identificatoire dans les prénoms composés : essai d’une description structurelle - Soufiane Lanseur (Multilinguales)
Identifying autonomy concerns compound first names with several parts identified as such. There are three different degrees of autonomy: absolute, relative or quasi-absence. The extended corpus used to carry out this study consists of 1018 first names, 226 of which are compound first names, in an attempt to answer the question of the structures of compound first names and their relationship with the degree of autonomy of the components. We came to the conclusion that first names whose components are absolutely autonomous have a simple juxtaposition relationship, whereas those whose parts are relatively autonomous have an obvious syntactic relationship of the characterised/characterising type. Names whose components are interdependent have more of a base/characterising relationship.